Perancangan Sistem Smart Home Menggunakan Internet of Things Hybrid - Sahrul Ramdani Nasution; Tata Sutarbi (Pusat Riset dan Inovasi Nasional, 2024)
Technological developments in the field of Internet of Things (IoT) have opened up broad possibilities for creating an efficient and intelligent smart home. Smart home systems connected to various devices via IoT can optimize comfort, security and energy efficiency